2021
DOI: 10.2147/ijn.s289515
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Radix Sophorae Flavescentis Carbonisata-Based Carbon Dots Against Ethanol‐Induced Acute Gastric Ulcer in Rats: Anti-Inflammatory and Antioxidant Activities

Abstract: Aim To explore the effects of Radix Sophorae Flavescentis carbonisata-based carbon dots (RSFC-CDs) on an ethanol-induced acute gastric ulcer rat model. Methods The structure, optical properties, functional groups and elemental composition of RSFC-CDs synthesized by one-step pyrolysis were characterized. The gastric protective effects of RSFC-CDs were evaluated and confirmed by applying a rat model of ethanol-induced acute gastric ulcers. The underlying mechanisms were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…[Typhaceae] (Yan et al, 2017), Juncus effusus L. [Juncaceae] , Sophora flavescens Aiton [Fabaceae] (Hu et al, 2021), Paeonia lactiflora Pall. [Paeoniaceae] (Zhao et al, 2020) and Phellodendron chinense C. K. Schneid.…”
Section: The Biological Activities and Mechanism Of Traditional Chine...mentioning
confidence: 99%
“…[Typhaceae] (Yan et al, 2017), Juncus effusus L. [Juncaceae] , Sophora flavescens Aiton [Fabaceae] (Hu et al, 2021), Paeonia lactiflora Pall. [Paeoniaceae] (Zhao et al, 2020) and Phellodendron chinense C. K. Schneid.…”
Section: The Biological Activities and Mechanism Of Traditional Chine...mentioning
confidence: 99%
“…Recently, Hu et al [ 115 ] showed Radix Sophorae Flavescentis carbonisata (RSFC)-based CDs against an ethanol-induced acute gastric ulcer in rats by inhibiting TNF-α and IL-6 releases via downregulation of NF-κB pathway. RSFC has been extensively harvested for treating ulcerative diseases throughout the body.…”
Section: Applications Of Hm-cdsmentioning
confidence: 99%
“…RSFC has been extensively harvested for treating ulcerative diseases throughout the body. The authors concluded that HM-CDs using high-temperature pyrolysis may have inherent bioactivities [ 115 ]. But the active ingredients are not revealed.…”
Section: Applications Of Hm-cdsmentioning
confidence: 99%
“…Due to the growing potential of CNDs in biomedical applications, studies have attempted to discern their use as therapeutic agents [30,[56][57][58][59][60][61].…”
Section: Therapymentioning
confidence: 99%